HUBUNGAN ANTARA KONDISI SOSIAL EKONOMI KELUARGA BURUH ROKOK DAN AKSESIBILITAS TEMPAT TINGGAL DENGAN PEMILIHAN SMP/SEDERAJAT UNTUK PUTRA-PUTRINYA - Ristiyani, Anisa (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2014)
This study aimed to: determine the socio-economic conditions and theaccessibility of a family residence cigarette workers who lived in the VillagePadurenan, determine the relationship between socio-economic conditions of thejunior high school/equivalent in child labor families cigarette, knowing therelationship between accessibility of residence with elections junior highschool/equivalent to child labor families cigarette. The population in this study isthe worker's family of labor cigarettes who have children are still in schooljunior high school/equivalent. The sample is taken by proportional randomsampling of the population is 46 people. Data collection using questionnairetechniques, interviews, and documentation. The data analysis technique used isdescriptive percentage (DP) and the chi-square test. Based on the results of theresearch there is a relationship between socio-economic conditions with theelection of junior high school/equivalent to their children, there is no relationshipbetween the accessibility of residence with election junior high school/equivalentto their child.